2022
DOI: 10.1128/cmr.00200-21
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Convalescent Plasma and Clinical Trials: Understanding Conflicting Outcomes

Abstract: Convalescent plasma (CP) recurs as a frontline treatment in epidemics because it is available as soon as there are survivors. The COVID-19 pandemic represented the first large-scale opportunity to shed light on the mechanisms of action, safety, and efficacy of CP using modern evidence-based medicine approaches. Studies ranging from observational case series to randomized controlled trials (RCTs) have reported highly variable efficacy results for COVID-19 CP (CCP), resulting in uncertainty.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 161 publications
2
79
0
Order By: Relevance
“…Multivariate analysis in our study showed that younger patients (<68 years) with less severe COVID-19 (i.e., admitted in low-intensity departments), where those who benefited the most from hyperimmune plasma-based therapy, particularly when it was administered early (<7 days from symptom onset) and at very high titer (>320). The latter finding is quite interesting as it confirms the most recent evidence from the literature showing a significant benefit of CCP among COVID-19 patients who received a larger amount of nAb [ 8 , 25 ].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Multivariate analysis in our study showed that younger patients (<68 years) with less severe COVID-19 (i.e., admitted in low-intensity departments), where those who benefited the most from hyperimmune plasma-based therapy, particularly when it was administered early (<7 days from symptom onset) and at very high titer (>320). The latter finding is quite interesting as it confirms the most recent evidence from the literature showing a significant benefit of CCP among COVID-19 patients who received a larger amount of nAb [ 8 , 25 ].…”
Section: Discussionsupporting
confidence: 81%
“…Besides the CCP variability, differences in study design, patients’ characteristics and disease severity could have played a role. Nevertheless, we would like to highlight that most of the published RCT showed signals of CCP efficacy, including reductions in mortality, when subgroup analyses were restricted to the early use of high-titer CCP [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further data collected from RCTs have, however, globally reported the lack of efficacy of CCP in seropositive patients hospitalized for severe COVID-19 [ 3 ], hence its use was discouraged by the World Health Organization (WHO) and many scientific societies [ 4 , 5 , 6 ] and has rapidly declined since the third pandemic wave. Contrary to this trend, based on the safety of CCP [ 7 , 8 ] and on the positive signals of efficacy in subgroup analyses from RCTs and non-RCTs, [ 9 ] the US Food and Drug Administration (FDA) approved the Emergency Use Authorization (EUA) for high-titer COVID-19 convalescent plasma to patients with immunosuppressive disease or receiving immunosuppressive treatment [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, there is an urgent need for novel therapeutic agents. COVID-19 convalescent plasma (CCP) has been initially investigated as a treatment for COVID-19 inpatients [ 4 ], but findings from randomized controlled trials (RCT) have consistently shown definite efficacy only in outpatients treated within 5 days from onset of symptoms [ 5 , 6 , 7 ]. This is in line with indications for the usage of any other antiviral, including small-chemical and anti-Spike mAbs.…”
mentioning
confidence: 99%